Sexual Functions Are Impaired in Males and Females With Chronic Spontaneous and Inducible Urticaria: A Controlled Study - Pelin Kuteyla Can; Utku Can (Dermatology Practical & Conceptual)
Introduction: Sexual dysfunction (SexD) related to chronic dermatologic diseases in women and men were reported in literature, but there are few reports on effects of chronic urticaria (CU) on male and female sexual functions.